Contaminant Diffusion along uniform flow velocity with pulse type input sources in finite porous medium - Dilip JAİSWAL; Yadav, R.R. (International Journal of Applied Methods in Electronics and Computers, 2014)
Solute transport inside  pore system occurs due to advection and diffusion which are the important mechanisms of contaminant transport in porous medium. Analytical solutions of one-dimensional advection-diffusion equation (the coefficient of second order space derivative being temporally dependent) are obtained in a finite domain for two sets of pulse type input boundary conditions. Initially the domain is not solute free. It is supposed uniformly distributed at the initial stage. The Laplace transform technique is used with the help of new space and time variables. The solutions are graphically illustrated and compared solute distribution  for finite and semi-infinite domain.